2018
DOI: 10.1097/aci.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific immunomodulators for recurrent respiratory tract infections, wheezing and asthma in children: a systematic review of mechanistic and clinical evidence

Abstract: Purpose of reviewTo provide an overview of the mechanistic and clinical evidence for the use of nonspecific immunomodulators in paediatric respiratory tract infection (RTI) and wheezing/asthma prophylaxis.Recent findingsNonspecific immunomodulators have a long history of empirical use for the prevention of RTIs in vulnerable populations, such as children. The past decade has seen an increase in both the number and quality of studies providing mechanistic and clinical evidence for the prophylactic potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(166 citation statements)
references
References 85 publications
(175 reference statements)
4
150
1
11
Order By: Relevance
“…❚ DISCUSSION Recurrent respiratory infections are common in pediatric healthy young patients, and may be triggered by different types of virus and bacteria. (11,14) In this study, with children without history of RRI, no beneficial effect was observed with the use of OM-85 BV. There was no significant difference in the number of respiratory infections nor in the use of antibiotics, visits to the emergency department, hospital admissions, and episodes of wheezing between the groups.…”
Section: ❚ Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…❚ DISCUSSION Recurrent respiratory infections are common in pediatric healthy young patients, and may be triggered by different types of virus and bacteria. (11,14) In this study, with children without history of RRI, no beneficial effect was observed with the use of OM-85 BV. There was no significant difference in the number of respiratory infections nor in the use of antibiotics, visits to the emergency department, hospital admissions, and episodes of wheezing between the groups.…”
Section: ❚ Resultscontrasting
confidence: 49%
“…(9) In addition to the preventive measures already proven to reduce recurrent respiratory infections (RRI), as promoting breastfeeding, adequate vaccination of children, vaccination of pregnant women, hygiene measures and tobacco-free environment, bacterial immunomodulators have been proposed as preventive intervention. (10,11) OM-85 BV is an immunostimulant used to prevent RRI. This immunostimulant contains 3.5mg per capsule of a lyophilized fraction of alkaline lysis of 21 strains of 8 species of common respiratory tract pathogens: Haemophilus influenza, Streptococcus pneumoniae, Klebsiella pneumoniae, Klebsiella ozaenae, Staphylococcus aureus, Streptococcus pyogenes, Streptococcus viridans and Neisseria catarrhalis.…”
Section: Registro Brasileiro De Ensaios Clínicos: Nº Rbr-9z764gmentioning
confidence: 99%
“…72,73 Strategies (microbial and others) to promote healthy epithelial barrier and the development of mucosal immune responses that can better resist viral infection might also help in preventing the development of asthma, as well as bacterial lysates, which may reduce the recurrent wheezing by increasing antiviral activity. 100 However, the level of evidence still remains to be low.…”
Section: Prevention Strategies Of Asthmamentioning
confidence: 99%
“…OM-85 is an oral immunomodulator the active principle of which is an extract of 21 bacterial strains of 5 different pathogenic respiratory bacterial genera (8 species and subspecies). Non-specific immunomodulation with bacterial lysate OM-85 to boost the body's natural defences against infection and to downregulate infection-and allergen-induced airway inflammation and airways hyper-reactivity provides a strategy for the management of rRTIs in at-risk (including atopic) children [14][15][16].…”
Section: Protection Of An Immunomodulator Against Airways Infections mentioning
confidence: 99%
“…For example, increased levels of IL-10 are associated with decreased airway inflammation, subsequent tissue remodelling and decreased hypersecretion. These effects combined with the reduced risk of rRTIs, which predispose to asthma and cause exacerbations, form the mechanistic framework for a reduced risk of these conditions [16,18]. The current standard of care in management of rRTIs in children is primarily focused on RTIs treatment including symptom relief [26,27].…”
Section: Downregulation In Chronic Inflammatory Statementioning
confidence: 99%